Fear, Growth, and Self-discovery: A Coming-of-Age Process in LUCY - Haze - Dimas Ramadhiansyah (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2024)
In the realm of music, especially within the K-pop genre, songs serve as dynamic mediums for addressing social issues. This research focuses on the `song